If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -7) = -4x + 20 Reorder the terms: -2(-7 + x) = -4x + 20 (-7 * -2 + x * -2) = -4x + 20 (14 + -2x) = -4x + 20 Reorder the terms: 14 + -2x = 20 + -4x Solving 14 + -2x = 20 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 14 + -2x + 4x = 20 + -4x + 4x Combine like terms: -2x + 4x = 2x 14 + 2x = 20 + -4x + 4x Combine like terms: -4x + 4x = 0 14 + 2x = 20 + 0 14 + 2x = 20 Add '-14' to each side of the equation. 14 + -14 + 2x = 20 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = 20 + -14 2x = 20 + -14 Combine like terms: 20 + -14 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 5v-89=2v+34 | | 3n+35=7n+35 | | 9w-10=2(w+9) | | 5+x^2=65 | | -2x+5=20-x | | 3x(x+2)=3x^2+4x-3+2x | | -3(5y-2)-y=-2(y-2) | | 23=3u+8 | | 8x-3.4=3x-6.7 | | -8d-d+7d=72 | | (w-4/-9)(-2/-3) | | -5(y-3)=-15 | | -8u+2(u+5)=16 | | 2x+3-5=5x-3+3x | | 7-4x=5x | | 2y+3(y-2)=29 | | C=240+0.75Y | | 3(x+4)=2(11-x) | | -2=6(x+3)-2x | | 284=-66a | | 4x^2+2x+1=o | | 2x-2=11-4x | | (X-5)^5/3-73=170 | | 10^6/10^2= | | n+1.2=7.4 | | Tan(28)=x/32 | | 4c-39=43c-78 | | 3(7+3x)=30 | | 5/3m=5/9 | | (q-12)(6q+1)=0 | | 150=x+1.5x | | 2/7×7/2x=424×2/7 |